Modern analytical electromagnetic homogenization with Mathematica® - Mackay, Tom G.; Lakhtakia, A. (Akhlesh), 1957- (IOP ebooks. 2020 collection., 2020)
This book is an overview of state-of-the-art analytical homogenization formalisms used to estimate the effective electromagnetic properties of complex composite materials. Beginning with an introduction to homogenization, the book progresses to cover both constitutive and depolarization dyadics. The homogenization formalisms for linear and non-linear materials are examined, followed by their applications and multiple examples using Mathematica code. This text is a valuable reference for PhD students and researchers working on the electromagnetic theory of complex composite materials.